La no tipificación del delito de la clonación de vehículo en el ecuador. - Ramírez Romero, Sergio Patricio (2013)
The information series engine and chassis and plate vehicles should be restricted in the National Traffic Agency, for the same must be authorized and managed by key, which would be the responsibility of a chief or departmental director or management. Detailing the chain of infringement in a scam buyers supposedly in good faith.